MEDICATION OVERUSE HEADACHE, WHY IT HAPPENED? - Restu Susanti (HUMAN CARE JOURNAL, 2020)
Medication Overuse Headache (MOH) is a secondary headache -- worsening condition of preexisting headache (usually primary hedache). MOH occurs due to medication overuse to relief the pain or to treat the headache attack. The etiology of MOH is the excessive use of single and combined analgesics, nonsteroidal anti-inflammatory drugs, caffeine, opioids, ergotamine, triptans and barbiturates. MOH is a chronic headache which need to recognize early. Diagnosis, accurate therapy, and management of comorbidities must be done to improve patient’s productivity and quality of life.